2015
DOI: 10.3389/fpls.2015.00403
|View full text |Cite
|
Sign up to set email alerts
|

Stress memory induced rearrangements of HSP transcription, photosystem II photochemistry and metabolism of tall fescue (Festuca arundinacea Schreb.) in response to high-temperature stress

Abstract: When plants are pre-exposed to stress, they can produce some stable signals and physiological reactions that may be carried forward as “stress memory”. However, there is insufficient information about plants' stress memory responses mechanisms. Here, two tall fescue genotypes, heat-tolerant PI 574522 and heat-sensitive PI 512315, were subjected to recurring high-temperature pre-acclimation treatment. Two heat shock protein (HSP) genes, LMW-HSP and HMW-HSP, exhibited transcriptional memory for their higher tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 57 publications
0
34
0
Order By: Relevance
“…Furthermore, it was reported that "stress memory" played a role in heat stress response regulation of turfgrass. After pre-acclimation with heat, HSP genes showed higher transcript abundance and photosynthetic efficiency in tall fescue during subsequent stress, implying an improvement in heat tolerance level [143]. MicroRNAs (miRNAs) are essential in transcriptional regulation, so investigation of the alteration of miRNAs under stress conditions is rather important to understand the response mechanisms of plants.…”
Section: Heat Stressmentioning
confidence: 99%
“…Furthermore, it was reported that "stress memory" played a role in heat stress response regulation of turfgrass. After pre-acclimation with heat, HSP genes showed higher transcript abundance and photosynthetic efficiency in tall fescue during subsequent stress, implying an improvement in heat tolerance level [143]. MicroRNAs (miRNAs) are essential in transcriptional regulation, so investigation of the alteration of miRNAs under stress conditions is rather important to understand the response mechanisms of plants.…”
Section: Heat Stressmentioning
confidence: 99%
“…Exogenous application of JA as well as its enhancement of endogenous levels by the overexpression of JA biosynthetic gene confers thermotolerance in Arabidopsis thaliana . Moreover, biosynthesis of plant metabolites, such as soluble sugars, amino acids, organic acids, and lipids, is also affected by high temperature; nevertheless, they are also crucial for plant adaptation to high‐temperature stress …”
Section: Introductionmentioning
confidence: 99%
“…12 Moreover, biosynthesis of plant metabolites, such as soluble sugars, amino acids, organic acids, and lipids, is also affected by high temperature; nevertheless, they are also crucial for plant adaptation to high-temperature stress. 9,13,14 To monitor heat stress-induced misfolded and damaged proteins, plant cells have evolved an elaborate protein quality control system consisting of molecular chaperones and protein degradation systems. 15,16 Heat-shock proteins (HSPs), the wellknown molecular chaperones, bind to denatured or non-native conformation proteins to prevent them from forming polymers, 17 while the protein degradation systems clear the damaged proteins.…”
mentioning
confidence: 99%
“…The I and P fluorescence intensities on the OJIP induction curve and the F300 parameter also decrease in wheat plants exposed to Pb stress (Kalaji and Loboda, 2007). Interestingly, tall fescue Festuca arundinacea leaves show a great decrease at all steps of OJIP and F300 parameters in response to high-temperature stress, but pre-acclimation treatment inhibit such declines (Hu et al, 2015). Intriguingly, Rapacz et al (2015) suggest that DI 0 /CS 0 values increase with increasing levels of PSII damage, which is the opposite to what we found (Fig.…”
Section: Discussionmentioning
confidence: 99%